2020
DOI: 10.1186/s12871-020-01056-0
|View full text |Cite
|
Sign up to set email alerts
|

The role of NMDA receptors in rat propofol self-administration

Abstract: Background: Propofol is among the most frequently used anesthetic agents, and it has the potential for abuse. The N-methyl-D-aspartate (NMDA) receptors are key mediators neural plasticity, neuronal development, addiction, and neurodegeneration. In the present study, we explored the role of these receptors in the context of rat propofol self-administration. Methods: Sprague-Dawley Rats were trained to self-administer propofol (1.7 mg/kg/infusion) using a fixed-ratio (FR) schedule over the course of 14 sessions … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 39 publications
1
6
1
Order By: Relevance
“…Our behavioural findings align with a previous study demonstrating that systemic pretreatment of MK801 significantly enhances the number of propofol infusions in self-administration behaviour. 25 Despite the concentration of dopamine in the NAc was not detected in this study, previous research has found that intra-NAc infusions of AP5 and MK-801 can enhance DA release, and the attenuation of excitatory amino acid that induces activation of GABA input to DA neurons in the VTA is thought to be the underlying mechanisms. [34][35][36] Besides, in vivo brain microdialysis studies show that propofol increases dopamine level in the NAc in rats in subanaesthetic and anaesthetic doses.…”
Section: Discussioncontrasting
confidence: 57%
See 3 more Smart Citations
“…Our behavioural findings align with a previous study demonstrating that systemic pretreatment of MK801 significantly enhances the number of propofol infusions in self-administration behaviour. 25 Despite the concentration of dopamine in the NAc was not detected in this study, previous research has found that intra-NAc infusions of AP5 and MK-801 can enhance DA release, and the attenuation of excitatory amino acid that induces activation of GABA input to DA neurons in the VTA is thought to be the underlying mechanisms. [34][35][36] Besides, in vivo brain microdialysis studies show that propofol increases dopamine level in the NAc in rats in subanaesthetic and anaesthetic doses.…”
Section: Discussioncontrasting
confidence: 57%
“…Previous research has demonstrated that NMDAR‐D1R/ERK/CREB signal transduction pathway is critical in the regulation of reward‐seeking behaviour 20 . It has been suggested that NMDARs may be involved in regulating propofol self‐administration 25 . The results indicate that intraperitoneally administered MK801, a non‐competitive channel blocker of NMDARs, facilitates propofol self‐administration behaviour in rats 25 .…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…Rats were trained to self-administer meth in operant chambers equipped with two "nose-poke" holes, a stimulus light above each hole, an audio tone generator and a house light. Nosepoking is an ethologically relevant behavior and a commonly employed operant task with rodents (e.g., Brown et al, 2020;Chen et al, 2020;Fredriksson et al, 2019;Gordon-Fennell et al, 2019;Hong, Kang, Chen, & Choi, 2019;Oliva & Wanat, 2019). Each operant chamber was enclosed in a ventilated, sound-attenuating chamber.…”
Section: Self-administrationmentioning
confidence: 99%